Approximate and information aspects of the numerical solution of unstable integral and pseudodifferential equations - Semenova, E. V.; Solodkii, S. G. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We present a review of the latest results obtained in the field of numerical solution of unstable integral and pseudodifferentialequations. New versions of fully discrete projection and collocation methods are constructed and justified. It is shown thatthese versions are characterized by the optimal accuracy and cost efficiency, as far as the use of computational resources isconcerned.